Orbital Stability of Solitary Waves of the Nonlinear Schrodinger-KdV Equation (Journal of Partial Differential Equations, 1999)
This paper concerns the orbital stability of solitary waves of the system of KdV equation coupling with nonlinear Schrödinger equation. By applying the abstract results of Grillakis et al. [1- 2] and detailed spectral analysis, we obtain the stability of the solitary waves.